PENGARUH DAUN JAMBU BIJI (PSIDIUM GUAJAVA) TERHADAP PENYEMBUHAN LUKA BAKAR GRADE II PADA TIKUS PUTIH WISTAR JANTAN - Sari, Melani Kartika; Aini, Efa Nur; Dewi, Sinta Triana (Jurnal Keperawatan Respati Yogyakarta, 2016)
In the wound care process it can be use a traditional medicine, include guava leaves. The aimed of the study is to identificate effectiveness care of the wound using guava leaves. The research are used true experiments by post-test with control group method on the sample and control group.  The sample consisted 12 subjects were selected by random sampling technique and divided into 2 groups. There are: Guava leaves’ treatment (n=6), and Control (n=6).The variable was measured in this research is a wound healing. This study use statistic test, Mann whitney U test with a level (p-value 0.05). The results of guava leaves and control are (p=value 0,004 less 0.05). Base on an average scores of the healing process, wound care using guava leaves were categorized in fast healing process The conclusion of the statistics treatment process by using guava leaves and control are different. Based on this research, it is recommended to do the wound care use guava leaves, considering the contents in (Guava leaves) are very useful as a cure burns and easy to apply. Keywords: wound of burns, guava leaves, wistar mice